2022
DOI: 10.3390/ijms232415806
|View full text |Cite
|
Sign up to set email alerts
|

Redox State of Human Serum Albumin in Multiple Sclerosis: A Pilot Study

Abstract: Like in many other pathologies, oxidative stress is involved in the development of neurodegenerative disorders. Human serum albumin (HSA) is the main protein in different body fluids including cerebrospinal fluid (CSF). By its redox state in terms of cysteine-34, albumin serves as marker for oxidative burden. We aimed to evaluate the redox state of HSA in patients with multiple sclerosis in serum and CSF in comparison to controls to identify possible correlations with disease activity and severity. Samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…So far, numerous in vivo studies have proved that the content of HSA-SH groups decreased in different pathological conditions compared to the control subjects or those who received some treatment [27,[34][35][36][37]. Contrary to this, there are a few in vivo studies in which HSA-SH group content changes were followed in real time [26], while there are many in vitro studies [5,30].…”
Section: Discussionmentioning
confidence: 99%
“…So far, numerous in vivo studies have proved that the content of HSA-SH groups decreased in different pathological conditions compared to the control subjects or those who received some treatment [27,[34][35][36][37]. Contrary to this, there are a few in vivo studies in which HSA-SH group content changes were followed in real time [26], while there are many in vitro studies [5,30].…”
Section: Discussionmentioning
confidence: 99%
“…Table S1 summarizes the results of studies related to markers of oxidative stress in the CSF from MS patients compared to controls [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Most of these studies found increased CSF levels of markers of lipid peroxidation, such as malonyl-dialdehyde, hydroxyalkenals, diene conjugates, 4-hydroxy-nonenal, oxidized phosphatidylcholine, and isoprostanes in patients diagnosed with MS compared to controls [ 13 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 45 , 46 , 47 ], with some exceptions [ 36 ].…”
Section: Oxidative Stress Markers In Patients With Multiple Sclerosismentioning
confidence: 99%
“…CSF levels of trace metals involved in oxidative stress processes were the subject of a single study, which described increased lead, decreased magnesium, and similar calcium, manganese, and zinc levels in patients with primary progressive MS (PPMS) compared to those with secondary progressive MS (SPMS) and controls [ 51 ]. The CSF human serum albumin (HAS), mercaptoalbumin (HMA), and non-mercaptoalbumins 1 and 2 (HNA1 and HNA2) [ 65 ] levels were reported to be similar in MS patients and controls. CSF neutrophil gelatinase-associated lipocalin (NGAL) was increased [ 39 ] or similar [ 38 ] compared to controls in two studies by the same group.…”
Section: Oxidative Stress Markers In Patients With Multiple Sclerosismentioning
confidence: 99%

Oxidative Stress Markers in Multiple Sclerosis

Jiménez-Jiménez,
Alonso-Navarro,
Salgado-Cámara
et al. 2024
IJMS
“…Albumin was fractionated by high performance liquid chromatography (HPLC) to give three peaks according to Cys-34 in the free sulfhydryl form (HMA), as a mixed disulfide (HNA1), or in a higher oxidation state (HNA2), as previously described. 19 Briefly, 20 μl of diluted plasma were injected into the HPLC system using a Shodex Asahipak ES-502 N 7C anion exchange column (7.5 Â 100 mm, Bartelt Labor-& Datentechnik, Graz, Austria) and 50-mM sodium acetate, 400-mM sodium sulfate, pH 4.85 as mobile phase. For elution, a gradient of 0%-6% ethanol and a flow rate of 1 ml/min were used.…”
Section: Oxidative Albumin Modificationmentioning
confidence: 99%